2007
DOI: 10.1677/jme-07-0039
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of hGH secretion in the presence of mutations of amino acids involved in zinc binding

Abstract: Zinc (Zn 2C ) binding by human GH through amino acid residues His18, His21, and Glu174 has been described as a prerequisite for GH dimerization and storage in secretory granules. Our aim was to investigate in vitro whether disturbed Zn 2C binding of mutant GH inhibits wild-type GH (wtGH) secretion and contributes to the pathogenetic mechanisms involved in dominantly transmitted isolated GH deficiency type II. Seven expression vectors harboring mutated human GH cDNAs were constructed in which nucleotide tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…wt-GH and/or different Zn 2ϩ -binding GH mutants were transiently expressed, and GH secretion and intracellular GH expression were analyzed in nonstimulated conditions after 48 hours of incubation. Both wt-GH secretion and intracellular GH accumulation remained unaffected when wt-GH was coexpressed with any of the Zn 2ϩ -binding GH mutants (including also double and triple mutants) (20). Interestingly, extracellular secretion and intracellular production of the GH mutants singly expressed in GH 4 C 1 cells was about 50% lower when compared with that of wt-GH, suggesting the role of Zn 2ϩ -binding residues in GH stability (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…wt-GH and/or different Zn 2ϩ -binding GH mutants were transiently expressed, and GH secretion and intracellular GH expression were analyzed in nonstimulated conditions after 48 hours of incubation. Both wt-GH secretion and intracellular GH accumulation remained unaffected when wt-GH was coexpressed with any of the Zn 2ϩ -binding GH mutants (including also double and triple mutants) (20). Interestingly, extracellular secretion and intracellular production of the GH mutants singly expressed in GH 4 C 1 cells was about 50% lower when compared with that of wt-GH, suggesting the role of Zn 2ϩ -binding residues in GH stability (20).…”
Section: Discussionmentioning
confidence: 99%
“…Cloning of human wt-GH in pcDNA3.1 (Ϫ) neo vector (Invitrogen) and generation GH Zn mutant (GH-H18A-H21A-E174A) was made as previously described (20).…”
Section: Expression Vectors and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential contribution of high-affinity Zn 2+ -binding residues in GH to the pathogenetic mechanisms involved in dominantly transmitted isolated GH deficiency type II was further studied by Iliev et al [38]. The production and extracellular secretion of wt -hGH transiently transfected in GH 4 C 1 cells (rat pituitary tumour cells) was compared to that of GH mutants in which the amino acids that bind Zn 2+ with high affinity were mutated to alanine in various combinations (Zn 2+ -binding GH mutants).…”
Section: The Biogenesis Of Gh Secretory Granules Begins With Zn2+-medmentioning
confidence: 99%
“…Importantly, in this study it was also demonstrated that Zn 2+ binding to GH would enhance the stability of the stored form (GH denaturation measured by guanidine hydrochloride at pH 8) and that the Zn 2+ -GH complex was more stable to denaturation when compared to monomeric GH [18]. In order to investigate further whether disturbed Zn 2+ binding of GH mutants (in which single, double or triple alanine substitutions at positions His18, His21 and Glu174 have been introduced) inhibits wt-GH secretion or production or if wt-GH and/or different GH mutants were transiently expressed in GH 4 C 1 cells [26]. The measurement of constitutive GH secretion (i.e.…”
Section: Dimerization Versus Oligomerization Of Gh By Zinc: Which Is mentioning
confidence: 99%